Designing Interactive Multimedia Courses Using STEAM Education - Pramono, Andy; Istiar Wardhana, Mitra; Samodra, Joko; Dewi Puspasari, Betty (KnE Social Sciences, 2022)
The Department of Design at the State University of Malang, Indonesia, has four study programs. Two of these are professional design study programs: the visual communication design undergraduate study program and the animation game diploma. In the curriculum of these two study programs there are interactive multimedia courses. With the number of students ranging from 750 at minimum, it is necessary to design a capable and innovative learning model for these interactive multimedia courses. STEAM education can be used as a framework to develop a lesson plan that is adaptable, benchmarked, and strongly reinforces learning standards in a unique and engaging way that improves student competence in the world of design professionals. This was descriptive research which used a procedural model development design. Borg and Gall explained that design development can be carried out through several stages, which were those used in this research, namely preliminary studies, research planning, initial product development, limited field tests, limited field test revisions, wider field test, feasibility test, revision of the results of the feasibility test, and dissemination and socialization of the final product. As a result of this research, a learning innovation was produced which combines several media and platforms, such as presentations, teaching materials, videos, mobile applications and WhatsApp. This learning innovation was implemented in the UM learning network information system (SIPEJAR) and the APK mobile application. Keywords: STEAM education, learning network information system, mobile application